The Influence of Work Skills and Physical Workload on Employee Performance at CV. Jaya Perkasa Abadi Palembang - Fitri Nurjanah Wati; Nina Fitriana; Yuni Adinda Putri (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
As of right now, one company category in Indonesia that is considered to never fail is printing. Due to societal advancement, printing services are becoming more and more necessary in today's world. In the actual world, this has been seen. For instance, printing and design services are needed by certain organizations in offices and other agencies to satisfy their demands for office supplies like business cards, identity or membership cards, letterheads, maps, and so on. Employee performance is the dependent variable in this study, whereas work skills and physical workload are the independent factors. There is a sample of 49 respondents in this quantitative research design. Non-probability sampling is the research method employed.